THE FACTORS THAT INFLUENCE VISITOR SATISFACTION IN CISAAT TOURISM VILLAGE SUBANG - Indira Putri; Sri Indah Nikensari (Yayasan Education and Social Center, 2023)
Tourism significantly contributes to the country's development, especially in economic growth. The tourism industry significantly declined in 2020 when the epidemic occurred, and implemented lockdown procedures worldwide. In Indonesia, tourism contribution decreased by about Rp. 27.5 billion to GDP. This research aims to analyze the factors that influence visitor satisfaction which in this study are seen in the three independent variables that affect the dependent variable. The independent variables in this study are attractiveness, facilities, and accessibility. At the same time, the dependent variable in this research is visitor satisfaction. The research method used in this study is used quantitative methods. The data collection technique was using a questionnaire. Respondents in this study were people who had visited Cisaat village with a minimum of 100 respondents. Questionnaires were distributed, and collected 121 respondents who have been tested with validity and reliability tests before trying data analysis. Based on the results of the validity and reliability tests, it is known that the measuring instrument used in this study is valid and reliable, so it is feasible to use as a measuring tool. Then the data analysis was used using multiple linear regression techniques. The study results showed that the variables of attractiveness, facilities, and accessibility positively and significantly affect visitor satisfaction in the Cisaat tourism village